INTERPRETASI EKOWISATA OLEH PEMANDU WISATA/ PRAMUWISATA PADA DAYA TARIK WISATA MANGROVE TOUR DI BALI - Izaati, Ismi Aliya; Dalem, A.A. Gde Raka; Joni, Martin (SIMBIOSIS, 2023)
Ecotourism is an activity that focuses on nature conservation, environmental sustainability and local community empowerment. Mangrove ecotourism educate visitors about the importance of preserving nature. Tour guides play important role in providing education through interpretation. This study aims to determine the quality of the interpretation given by the tour guide to visitors, as well as the type of interpretation and interpretation facilities used by the tour guide. The research was conducted at Taman Hutan Raya (Tahura Ngurah Rai), and HPI Bali from January – June, 2022. The methods used are observation, documents examination and interviews. The interviewed guides were 26 people, and distributing questionnaire to 50 tourists. This study found that the types of interpretations that are used by Tahura Ngurah Rai tour guides and HPI are 9 types, interpretation facilities that are used by Tahura Ngurah Rai tour guides are 15 facilities and HPI as many as 15 facilities. The interpretation quality of Tahura Ngurah Rai tour guides was  good (score 77%) and HPI tour guides was also good (score 75%). The tourist's satisfaction was excellent (score 84.4%). Aspects that affect the quality of tour guide interpretation include education, training, and experience. The expected benefits of this research was it could educate tourists and tour guides about importance of quality interpretation on tourists’ perceptions and attitudes.